Pengaruh Pendidikan, Pengalaman Kerja dan Pelatihan terhadap Efektivitas Penggunaan Sistem Informasi Akuntansi - Ningtias, Pinky Dwi; Diatmika, I Putu Gede (Universitas Pendidikan Ganesha, 2021)
Accounting information systems have been widely applied to companies and organizations alike. However, there is often considerable damage to the company and its employees in the practice. The goal is to find out how variable levels, employment experiences and employee training affect the effectiveness of the use of accounting systems. The research facility, pt. Panca multiprime partner, has taken a sample of 38 respondents. Samples are determined by a pusposive sampling technique. The process of obtaining data by spreading over the questionnaires to the responders. Data obtained are then treated based on data quality tests, classic assumptions and hypothetical tests using version 25 help. The study results that the level of education cannot affect the effectiveness of the use of accounting information systems because it does not ensure that a person can maximize his or her ability. While employment experiences and employee training can significantly affect the effectiveness of the use of accounting information systems. Training and experience can maximize system user performance.